Linking Form and Meaning - Rudanko, J. author. aut Link
X, 110 p.
Keywords: This book documents changes and trends in English predicate complementation. In-depth case studies of grammatical patterns presented here uncover new links between form and meaning in these constructions, offering fresh insights into explanatory principles to account for variation and change in the system of English predicate complementation.